Integrating the GRACE Score with the Ceramide Risk Score Enhances the Predictive Accuracy of Major Adverse Cardiac Events in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Xiaofei Wang; Chengzhe Liu; Fu Yu; Zizhuo Zhang; Jiale Wang; Xiaoyu Shi; Tianyou Xu; Qiang Deng; Liping Zhou; Wanyue Sang; Hong Jiang; Lilei Yu (Reviews in Cardiovascular Medicine)
Background: Ceramide, a key molecule in sphingolipid metabolism, is recognized as a standalone predictor of long-term major adverse cardiac events (MACE). We explore if integrating the global registry of acute coronary events (GRACE) score with the ceramide risk score (ceramide test 1, CERT1) improves MACE prediction in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). Methods: This cohort study included 210 participants with ACS undergoing PCI. MACE was defined as the recurrence of non-fatal acute myocardial infarction, repeat coronary revascularization procedures (PCI or coronary artery bypass grafting, CABG), or death excluding the initial event qualifying the patient for the study. The cumulative incidence of MACE was analyzed using the Kaplan-Meier method. Both univariate and multivariate Cox regression analyses identified MACE predictors. The predictive accuracy of combining the GRACE score with the CERT1 score was assessed using the area under the receiver operating characteristic curve (AUC), integrated discrimination improvement (IDI), and net reclassification improvement (NRI). Results: During the 12-month follow-up period, 35 of the 210 participants experienced a MACE. The Kaplan-Meier analysis revealed a significant variation in MACE incidence stratified by the CERT1 score (χ2 = 21.344, p < 0.001). Multivariate Cox regression analysis identified low-density lipoprotein (p = 0.002), quantitative flow ratio (p = 0.013), the CERT1 score (p = 0.005), and the GRACE score (p = 0.007) as independent predictors for MACE. Integrating the GRACE score with the CERT1 score improved prediction accuracy, raising the AUC from 0.733 to 0.834. This adjustment provided a more precise risk reclassification and discrimination between patients likely and unlikely to experience MACE (NRI: 0.526, p = 0.004; IDI: 0.120, p < 0.001). Conclusions: The CERT1 score independently predicts long-term MACE for individuals diagnosed with ACS undergoing PCI. Including the CERT1 score significantly enhances the GRACE score's capacity to risk-stratify these patients. Clinical Trial Registration: Registration number: ChiCTR2300068491 (https://www.chictr.org.cn/showproj.html?proj=180370).